Evolving antibody evasion and receptor affinity of the Omicron BA.2.75 sublineage of SARS-CoV-2 - Qian Wang; Zhiteng Li; Yicheng Guo; Ian A. Mellis; Sho Iketani; Michael Liu; Jian Yu; Riccardo Valdez; Adam S. Lauring; Zizhang Sheng; Aubree Gordon; Lihong Liu; et al. (iScience, 2023)
Summary: SARS-CoV-2 Omicron BA.2.75 has diversified into multiple subvariants with additional spike mutations and several are expanding in prevalence, particularly CH.1.1 and BN.1. Here, we investigated the viral receptor affinities and neutralization evasion properties of major BA.2.75 subvariants actively circulating in different regions worldwide. We found two distinct evolutionary pathways and three newly identified mutations that shaped the virological features of these subvariants. One phenotypic group exhibited a discernible decrease in viral receptor affinities, but a noteworthy increase in resistance to antibody neutralization, as exemplified by CH.1.1, which is apparently as resistant as XBB.1.5. In contrast, a second group demonstrated a substantial increase in viral receptor affinity but only a moderate increase in antibody evasion, as exemplified by BN.1. We also observed that all prevalent SARS-CoV-2 variants in the circulation presently, except for BN.1, exhibit profound levels of antibody evasion, suggesting this is the dominant determinant of virus transmissibility today.